Psychosocial Factors Associated with Coping Mechanisms among Adolescents: The Role of Family Support and Self-Efficacy - Reni Nurhidayah; Meindia Bintang Audisya; Dhita Kurnia Sari (Universitas STRADA Indonesia, 2026)
Adolescence is a developmental stage characterized by significant psychological and social changes that may increase vulnerability to stress. Effective coping mechanisms are essential for adolescents to manage academic and social pressures. Psychosocial factors, particularly family support and self-efficacy, play an important role in shaping adolescents’ adaptive responses to stress. This study aimed to examine the association between family support, self-efficacy, and coping mechanisms among adolescents. A quantitative correlational study with a cross-sectional design was conducted among 193 students at a vocational high school in Tulungagung, Indonesia. Participants were selected using stratified random sampling. Family support was measured using the Family Support Scale (FSS), self-efficacy using the Self-Efficacy Questionnaire for Children (SEQ-C), and coping mechanisms using the Adolescent Coping Orientation for Problem Experiences (A-COPE). Data were analyzed using Spearman’s rho correlation test with a significance level of 0.05. The findings indicated that most adolescents reported moderate levels of family support (38.3%) and self-efficacy (38.9%), while coping mechanisms were predominantly moderately adaptive (53.9%). Statistical analysis revealed a significant positive association between family support and coping mechanisms (r = 0.799; p < 0.001) as well as between self-efficacy and coping mechanisms (r = 0.654; p < 0.001). Higher levels of family support and self-efficacy were associated with more adaptive coping strategies among adolescents. In conclusion, family support and self-efficacy are important psychosocial factors associated with adolescents’ coping mechanisms. Strengthening emotional support within families and enhancing adolescents’ self-efficacy may contribute to improved adaptive coping and mental well-being.